PETROLOGY AND ECONOMIC MINERAL INVESTIGATION IN KAR GAH VALLEY, KOHISTAN ISLAND ARC, GILGIT, PAKISTAN - Majeed Ullah,; Akbar Ali,; Tahseen Ullah Khan,; Mujahid Ahmed Khan,; George Kontakiotis,; Assimina Antonarakou, (Spectrum of Engineering Sciences, 2025)
This study investigates the petrology and economic mineral potential of the Kar Gah Valley, located within the Kohistan Island Arc in Northern Pakistan. The primary aim of this research is to explore the geochemical and mineralogical characteristics of the region, focusing on polymetallic mineralization, including gold, copper, and other base metals. The study employs a combination of field sampling, petrographic analysis, atomic absorption spectroscopy (AAS), and X-ray diffraction (XRD) to examine rock and stream sediment samples collected from the area. The findings reveal significant concentrations of gold, silver, copper, lead, zinc, and other trace metals in both rock and sediment samples, suggesting the presence of polymetallic vein-type mineralization. The highest concentration of gold was found in the KCS6 sample (14.64 ppm), accompanied by elevated levels of copper and other metals. Petrographic and XRD analyses confirmed the presence of hydrothermal alteration, with minerals such as chlorite, epidote, and biotite indicating low-grade metamorphism consistent with hydrothermal fluid activity. The results highlight the economic potential of the Kar Gah Valley as a prospective region for gold and copper mining, with fracture-controlled polymetallic mineralization being the most prominent feature. The study concludes by emphasizing the need for further exploration and drilling to fully assess the mineralization's extent and economic viability.